The process of selecting and prioritising corporate sustainability issues: Insights for achieving the Sustainable Development Goals. (1st November 2019) - Ike, Masayoshi; Donovan, Jerome Denis; Topple, Cheree; Masli, Eryadi Kordi
Abstract: The Sustainable Development Goals are a set of 17 wide ranging goals that articulates the desired outcome of sustainable development. The private sector is a key factor in achieving these goals through actions of corporate sustainability. However, there is a paucity of research regarding the application of Sustainable Development Goals at the firm level and it remains unclear how the private sector can operationalise and achieve the goals through corporate sustainability. While every Sustainable Development Goal is deemed of equal importance, it is up to individual firms to interpret and prioritise their implementation. Using a case study approach, this paper identified the specific goals considered by Japanese manufacturing multinational enterprises as a priority when establishing or significantly expanding operations in developing countries. The methodology employed allowed the retrospective analysis of corporate sustainability data through a Sustainable Development Goal lens. In-depth, semi-structured interviews were carried out with 58 respondents from 16 sample firms operating in the Philippines, Indonesia, Thailand and Vietnam. The results show the multinational enterprises in the sample focus on a particular set of Sustainable Development Goals when establishing, or significantly expanding, subsidiary operations in the Philippines, Indonesia, Thailand and Vietnam. The findings show policy makers in the host countries should ensure Sustainable Development Goals such as education and strong institutions are in place to attract multinational enterprises to their shores. Other stakeholders such as non-governmental organisations and the community were also seen to influence the prioritisation of certain goals considered by firms.